External validation of the TiPS65 score for predicting good neurological outcomes in patients with out-of-hospital cardiac arrest treated with extracorporeal cardiopulmonary resuscitation. (January 2023) - Makino, Yuto; Okada, Yohei; Irisawa, Taro; Yamada, Tomoki; Yoshiya, Kazuhisa; Park, Changhwi; Nishimura, Tetsuro; Ishibe, Takuya; Kobata, Hitoshi; Kiguchi, Takeyuki; Kishimoto, Masafumi; Kim, Sung-Ho; et al.
Abstract: Aim: Estimating prognosis of patients treated with extracorporeal cardiopulmonary resuscitation (ECPR) is essential for selecting candidates. The TiPS65 score can predict neurological outcomes of patients with out-of-hospital cardiac arrest (OHCA) treated with ECPR. We aimed to perform an external validation of this score. Methods: Data from the Japanese Association for Acute Medicine Out-of-Hospital Cardiac Arrest registry, a multicentred, nationwide, prospectively registered database, were analysed. All adult patients with OHCA and shockable rhythm and treated with ECPR between January 2018 to December 2019 were included. In the TiPS65 score, age, call-to-hospital arrival time, initial cardiac rhythm at hospital arrival, and initial pH value were used as predictors. The primary outcome was 30-day survival with favourable neurological outcomes (Cerebral Performance Category 1 or 2). Discrimination, using the C -statistic, and predictive performances of each score, such as sensitivity and specificity, were investigated. Results: Of 590 included patients (517 [81.6%] men; median [interquartile range] age, 60 [50–69] years), 64 (10.8%) reported favourable neurological outcomes. The C -statistic of the TiPS65 score was 0.729 (95% confidence interval (CI): 0.672–0.786). When the cut-off of TiPS65 score was set to >1, the sensitivity and specificity were 0.906 (95%CI: 0.807–0.965) and 0.430 (95%CI: 0.387–0.473), respectively; conversely, when the cut-off was set to >3, they were 0.172 (95%CI: 0.089–0.287) and 0.971 (95%CI: 0.953–0.984), respectively. Conclusions: The TiPS65 score shows reasonable discrimination and predictive performances. This score can be supportive in the decision-making process for the selection of eligible patients for ECPR in clinical settings.